Case Report: Anti-NF186+ CIDP After Receiving the Inactivated Vaccine for Coronavirus Disease (COVID-19) - Wen, Shirui; Huang, Kailing; Zhu, Haoyue; Li, Peihong; Zhou, Luo; Feng, Li (Frontiers in Neurology, 2022)
COVID-19, the novel coronavirus disease, has been spreading worldwide. Vaccination can significantly reduce the mortality rate caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). There are several effective vaccines that have been introduced. Inactivated COVID-19 vaccine is one of these options and generally considered safe. We report a rare case of anti-NF186+ chronic inflammatory demyelinating polyneuropathy (CIDP) in a 23-year-old male patient who was vaccinated with inactivated COVID-19 vaccine. This report adds a possible rare side effect of a COVID-19 vaccine and provides a case for the clinical effectiveness of rituximab in patients with anti-NF186+ CIDP.